Postoperative Foot Massage for Patients after Caesarean Delivery - Xue, M.; Fan, L.; Ge, L. N.; Zhang, Y.; Ge, J. L.; Gu, J.; Wang, Y.; Chen, Y. (Zeitschrift für Geburtshilfe und Neonatologie, 2016)
Objective: Little evidence is available on complementary therapies for anxiety and pain relief after caesarean delivery. The purpose of this study was to evaluate the effects of foot massage post-operatively in patients after caesarean delivery.Materials and methods: 70 patients were divided to the study or control group after cesarean delivery. Patients in the study group had foot massages for 20 min after surgery. All patients underwent heart rate variability analysis (HRV) and scored their anxiety; pain intensity was evaluated using an 11-point numerical rating scale (NRS).Results: In the study group the HRV, as measured by the low frequency power (LF) value and the LF-to-high frequency power (LF/HF) ratio during Holter assessment, was significantly less after foot massage intervention, but was not changed in the control group. Moreover, the HF value significantly increased and the anxiety score significantly decreased after foot massage intervention, but not in the control group. The pain intensity score obtained 60 min after the massage was significantly lower in the study group than the control group, as were the vital signs (respiratory rate, and systolic and diastolic blood pressure).Conclusion: Post-operative massage intervention can reduce anxiety and pain in patients after caesarean delivery.
Keywords: cesarean delivery; massage intervention; heart rate variability; numerical rating scale